Effects of Mother's Home Time on Children's Schooling - Datcher-Loury, Linda (The Review of Economics and Statistics, 1988)
In order to determine the importance of parental time inputs in the intergenerational transmission of socioeconomic status, previous work relies on proxies such as family size, birth order, maternal employment, and retrospective reports of child care time. This paper is unique in finding a connection between more direct measures of mother's child-care time and children's outcomes as adults. It shows that (1) higher home productivity increases, but higher opportunity costs reduce, maternal child-care time and (2) greater child-care time of highly-educated, but not of less well-educated, mothers significantly raises children's years of schooling. Copyright 1988 by MIT Press.